Vibration Control Using Modern Control System for Hybrid Composite Flexible Robot Manipulator Arm - Sengalani, Ramalingam; S, Rasool Mohideen (Journal of Automation, Mobile Robotics and Intelligent Systems, 2023)
In this research, a model of a robotic manipulator flexible structure and an equation of motion for controller design is planned. The structural material for the robot structure is chosen as a hybrid composite for this investigation along with a comparison study is carried out for the aluminium 6082 alloy of flexible manipulator arm application. To analyses, the vibration behavior and control implementation by adding joint flexibility in the system is organized. Using simulation algorithm, system parameter calculation is carried out through MATLAB software for vibration amplitude, transient period, steady-state error, and settling time of flexible robotic arm system. In a systematized way of motion equation, flexible robotic deflections are organized via the assumed mode (AM) and Lagrange techniques (LT). The graph analysis of hybrid composite and AL6082 materials with high stiffness coefficients is plotted. These obtained values from the plot are utilized for Linear Quadratic Regulator (LQR) controller design. The LQR output facts for both aluminium structural robotic arm and composite material robotic arms are established.